Gastric Outlet Obstruction following Recurrent Pancreatitis Uncovers A Giant Parathyroid Adenoma: A Case Report - Singh, Brijesh; GA, Toshib; Rathore, Yashwant; Agarwal, Shipra; Chumber, Sunil; Damle , Nishikant (Journal of the ASEAN Federation of Endocrine Societies, 2022)
A 35-year-old female presented with abdominal pain, fever, projectile vomiting, and a diffuse tender epigastric mass. She was diagnosed to have acute persistent pancreatitis with a pancreatic pseudocyst. Elevated serum calcium levels provided an etiologic link between hypercalcemia and pancreatitis. On examination, a nodule was found in the left side of her neck which was later diagnosed as a giant left inferior parathyroid adenoma. This report highlights the critical analysis of history, examination, and investigations to reach an ultimate diagnosis. Pseudocyst drainage and parathyroidectomy resolved her symptoms.